Towards « Participative » Multinationals - Warner, Malcolm; Peccei, Riccardo (Relations industrielles / Industrial Relations, 1977)
If the labour movement is strong, this may not only simultaneously make for more effective participation at the National plant levels, but also via pressure on the State, to very much limit the role of the multi-national corporations.